Stylization Process In The Presentation Of Ratib Saman Dance As An Effort To Preserve Malay Culture In Sambas, West Kalimantan - Ismunandar Ismunandar; Hartono Hartono; Chairil Effendy; Restu Lanjari (International Conference on Science, Education, and Technology, 2023)
Ratib Tari Saman was one of the local variability of endangered Sambas. Dance in Sambas Regency is controlled by the elders, who were taught the parents in the previous generation, while the need to educate young people in Sambas very difficult. This research used a qualitative research design. The method used in this research is descriptive method. The approach that is specifically shorting anthropology anthropology of dance. Data in this study is the information about traditional dance Ratib Suit Sambas Malay community. Qualitative data analysis, data sources, and H. Abdul Hadi Djase who know about dance in the village Sebadi Ratib suit, with at least. The data is the result of interview, observation and documentation. Based on the results of the research can be summarized as follows. Tari Saman Ratib in berobat village is an application for help from the shelter to avoid the various threats addressed to Allah SWT.